DISTRIBUTION OF SOFT CORALS OF THE ALCYONIIDAE FAMILY IN THE FORE REEF ZONE ON BARRANGLOMPO ISLAND, MAKASSAR CITY - Muhammad Fahmi Djunaid Ashari; Chair Rani; Aidah A Ala Husain (Hasanuddin University, 2025)
This study aimed to identify the types of soft corals of the family Alcyoniidae based on their morphological characteristics and spicule shape; determine the composition of the type and vertical distribution of soft corals; and analyze the relationship between the distribution of soft corals of the Alcyoniidae family in the fore reef zone with environmental factors in the waters of Barranglompo Island. This research was conducted in the coral reef area on the edge of Barranglompo Island which is divided into four observation stations. Data on species and the number of soft coral colonies were collected using the 100-meter belt transect method, which was placed parallel to the shoreline at two depths. This study identified 23 soft coral species belonging to three genera: Sinularia, Lobophytum, and Sarcophyton. Five spicule models were found: clubs, capstan, shuttel, spindle, and barrel, and the dominant one was the shape of clubs. There was no significant difference in the number of types between the research stations in the upper and lower reef zones. The density of soft corals differed markedly between stations in the lower fore reef zone, with the highest density of 0.19 ind/m2 at the southern station of the island. The high density of soft corals was located in the southwest of the island in the upper and lower fore-reef zones andwass associated with high light intensity and salinity. The high richness of soft coral types is located in the southeast of the island in the upper and lower fore-reef zones, which are characterized by turbidity values and high temperatures.